Peran dan Potensi Sawah Bengkok dalam Meningkatkan Kesejahteraan Ekonomi Masyarakat Dusun Wage Desa Cileuleuy - Sadali, Munawir; Anggraeni, Maura Tia; Maula, Nala Ni’matul; Maulana , Muhammad Adrian Maulana (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Bengkok rice fields in Wage Hamlet, Cileuleuy Village, play an important role in supporting the economic welfare of the local community. It serves as a source of income for village officials and the farmers who manage it. This research uses descriptive qualitative methods to analyse the role of bengkok rice fields in improving the economic welfare of the community, as well as the challenges faced in their management. The results show that although sawah bengkok is a major source of income for the community, agricultural productivity is still hampered using traditional methods and fluctuations in commodity prices. Efforts are needed to diversify commodities and apply modern agricultural technology to increase yields and economic sustainability.